COMMUNITY POLICING AS A PANACEA FOR INSECURITY IN NIGERIA: LESSONS FROM THE BIU EXPERIENCE - Jacob, Makbere Arthur; Jacob, Anto Bidda; Ibrahim, Ado Ahmad (African Journal of Social and Behavioural Sciences, 2024)
Nigeria has witnessed unprecedented waves of security challenges across its six geopolitical zones. From ethno-religious and farmer-herder crises to insurgency and separatist movements, the escalation of insecurity threatens the nation’s stability and development. Therefore, this study examined the effectiveness and challenges of Biu community policing (Yan Gora) on the security of Biu, Borno state. Functionalist theory was used as the theoretical orientation of the study, the study adopted a survey research design while purposive sampling was used with 200 questionnaires administered. The findings of this study revealed that Yan Gora, hunters, and vigilante group/CJTF are the only recognized community policing apparatus in Biu. It was also discovered that without this security apparatus, the formal law enforcement agencies will find it difficult to address the security challenges in Biu. This study also found that some of the challenges impeding the effectiveness of this informal security apparatus include, inadequate membership development, corruption and lack of confidentiality. Therefore, the study recommends the need for government to introduce, support and, if possible, pass the law for the institutionalization of other security mechanisms such as community policing in order to enhance and ameliorate the deteriorating security situation in the country.